Warfarin-Induced Pulmonary Hemorrhage: A Rare and Life-Threatening Complication in the Resource-Limited Setting of Gaza - Abdallah Abu Shammala; Majed Jaber; Bilal Irfan; Alaa Owda; Abdallah Herzallah (Case Reports in Pulmonology)
Warfarin is widely prescribed for the prevention of thromboembolic events but carries a well-known risk of bleeding complications. While gastrointestinal and intracranial hemorrhages remain among the more frequent sites, pulmonary hemorrhage is an exceedingly rare case presentation and can be particularly catastrophic. We report the case of a 57-year-old male in Gaza with an extensive medical history of past hospitalization, who presented with severe ecchymosis, with his condition progressing to life-threatening pulmonary hemorrhage. This case occurred amid an active Israeli military assault in November 2024 in the European Gaza Hospital in Khan Yunis, at a time when diagnostic modalities had become limited or completely destroyed and healthcare resources were in severe shortage. The patient was treated with supportive measures, including mechanical ventilation and warfarin reversal using vitamin K and fresh frozen plasma. His anticoagulation regimen was changed to rivaroxaban. This case underlines the difficulties in diagnosing and managing rare but critical hemorrhagic complications in conflict-affected regions and emphasizes the urgency for clinicians to be vigilantly monitoring international normalized ratio values to conduct timely interventions.